A mobile app for wound cleansing - Salome, Geraldo Magela; Lino, Luiz Augusto Mota (Saúde (Santa Maria), 2024)
Objective: To develop a mobile application (app) to assist health professionals in the cleansing of wounds. The app aids in the evaluation of the wound and recommends wound cleansing procedures according to the wound characteristics.Methods: A contextualized instructional design was used in the development of a mobile app. A literature search was carried out to identify relevant studies for its construction. The development of the mobile app included the selection of multimedia app tools, definition of the navigation structure, planning of the environment configuration, and building of an environment for downloading the app to the mobile device.Results: The literature search yielded 15 articles. A mobile app was created with an easy-to-use graphic interface. The application stores the patient’s demographic and clinical information, health professional’s information, clinical evaluation of the wound, and recommends wound cleansing procedures and cleansing agents.Conclusion: The mobile app may be used in clinical practice to assist health professionals in the cleansing of wounds and in the selection of nursing interventions according to the different types of tissue, as well as in nursing education.